Pengaruh Financial Technology (Fintech) Dan Literasi Keuangan Terhadap Kinerja Perusahaan Pada PT. Bank Rakyat Indonesia (Persero) Tbk Cabang Kota Bandar Lampung - Raditya Purnamasari; Yulistina Yulistina; Maria Septijantini Alie (CV. Ulil Albab Corp, 2024)
The development of Financial Technology (FinTech) has changed the global banking and financial landscape and influenced company performance, as seen in PT. Bank Rakyat Indonesia (Persero) Tbk Bandar Lampung City Branch. This research uses a quantitative approach to explore the impact of FinTech and Financial Literacy on company performance. Data was collected from 1 branch with 165 employees selected by purposive sampling in February 2024. The results show a positive and significant simultaneous influence between FinTech and Financial Literacy on company performance. The F test shows an Fcount value of 128.595, exceeding the Ftable value of 3.05, and a significance of 0.00 < 0.05, so the alternative hypothesis is accepted. Partial analysis shows FinTech's t count of 5.530 and Financial Literacy's 7.920, both exceeding the t table of 1.974, with a significance value of 0.00 < 0.05, so the alternative hypothesis is accepted. This means that increasing both FinTech and Financial Literacy has a positive impact on company performance. Keywords : FinTech, Financial Literacy, Company Performance, Bank Rakyat Indonesia (BRI).